Towards Logical Clocks in P2P-based MMVEs - Weis, Torben; Wacker, Arno; Schuster, Sebastian; Holzapfel, Sebastian (Electronic Communications of the EASST, 2009)
A crucial requirement for peer-to-peer-based Massively Multiuser Virtual Environments (P2P-based MMVEs) is the accurate and reliable synchronization of actions among the users (processes). To do so, clock synchronization protocols can be used. In this paper we first analyze the usage of standard vector clocks for this purpose and show their deficits (e.g. growing large). Then we present a novel variation of vector clocks – pruned vector clocks – which overcome the deficits of standard vector clocks and are therefore suited for their usage in MMVEs. The basic idea of pruned vector clocks is to prune all entries in a vector clock, which are not relevant at some point in time. We show, that with this approach vector clocks will stay constant in size and still provide the necessarily synchronization among the processes.